Socio-Economic Characteristics of Adult Female Perpetrators of Criminal Offences in the Republic of Serbia - Radović-Stojanović, Jelena V; Tomić, Marta; Mićović, Marija (NBP. Nauka, bezbednosti, policija, 2023)
The subject of this paper is the research of socio-economic characteristics of adult female perpetrators of criminal offences in the Republic of Serbia. The following characteristics of adult women perpetrators have been observed: age, marital status, education, employment status, occupation. The structure of women perpetrators according to the mentioned characteristics, calculated as a percentage share of the observed characteristics of female perpetrators and their modalities in the total number of female perpetrators has been analyzed. The comparative analysis has been made with the corresponding structures for adult male perpetrators of criminal offences and for the total population of the Republic of Serbia. In the research data from the Statistical Office of the Republic of Serbia for 2021 from the field of Judiciary were used. The research covered the most common crimes: criminal offences against life and limb, criminal offences against marriage and family, criminal offences against property, criminal offences against the economy, criminal offences against human’s health and criminal offences against public peace and order. The results of the research reveal poor socio-economic status of adult female perpetrators, indicating the strong influence of socio-economic status on crime of female perpetrators in the Republic of Serbia.